Pengaruh Serat Alami Terhadap Tingkat Kepadatan dan Intensitaskeretakan Tanah Lunak Pada Siklus Basah Kering - Nurdin, Sukiman; H. Ahmad, Sulaiman (JOURNAL TEKNIK SIPIL DAN INFRASTRUKTUR, 2017)
The use of natural fibers as a reinforcement material in clay becomes an alternative choice of materials widely used in the early decades of soil improvement techniques. This practice is to improve soil strength and resistance to cracks. This preliminary practice was done because the cost of procurement is relatively low cost and also available in almost all areas of Indonesia. Modification of the use of natural fiber with other materials such as synthetic fiber materials has begun to do a lot at this time. The objectives of this research are: (1) Analyzing the physical and mechanical of soft soil mineralogy characteristics, (2) Analyzing the soft soil mechanical behavior by reinforcing  the Palm oil  fiber  (POF) of  the empty fruit bunch of palm oil whether it can increase soft soil capacity, (3) shrinkage and crack intensity factor (CIF) of soft soil in wet-dry cycles. The results showed that the addition of natural fiber on soft soil tends to reduce the level of soil density and increase the water content of the soil, although not too large. The effect is only about max 2.35% on 2% fiber content. While the swelling potential and shrinkageof the soils can be reduced by fiber reinforcement. In the crack potential test showed a substantial reduction of  crack intensity factor, whereas the addition of fibers in the soft soil can reduce cracks up to 444%. This shows that the fiber-soil has great ability in resisting the tensile strength of the soil-fiber interface due to the adhesion properties so that the soil is not easily cracked